UTILIZATION OF INFORMAL SOURCES SYSTEM FOR STRENGTHENING MANINGKAMU FOR CONFLICT RESOLUTION IN THE HATUHAHA AMARIMA COMMUNITY IN HARUKU ISLAND, CENTRAL MALUKU REGENCY - Lawalata, Cornelly M. A.; Nulhaqim, Soni A.; Darwis, Rudi Saprudin; Gunawan, Wahyu (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Social Welfare Source System can be values that already exist embedded in the community so that they can be explored and used to meet needs and solve social problems faced, including conflict resolution in the community. The Hatuhaha Amarima community, which has experienced repeated conflicts, ignores its own resource system and is not optimized by the local community. So far, conflict resolution has only been in the process of traditional ceremonies, namely maningkamu, and has not involved all components of the community so that they experience repeated conflicts. Therefore, in providing reinforcement to your maningkamu, there are several alternatives that can be used as a form of action that can complement the shortcomings or weaknesses of your maningmu as a conflict resolution effort. One such alternative is the informal sourcing system. This study aims to describe the benefits of informal sourcing systems in society and provide reinforcement for your maningkamu to contribute to conflict resolution with a qualitative descriptive research design.The results showed that the contribution of the informal source system was used to strengthen the Hatuhaha Amarima community, namely the "maningkamu" custom, for conflict resolution. Values, Maningkamu which are rich in the characteristics of brotherhood, kinship, family ties, can be further optimized and contribute to permanent conflict resolution. According to Pincus and Minahan, the potential resources possessed can empower and optimize family values to unite all components such as friends, neighbors and people who are willing to help to solve a social problem, provide emotional support, affection, advice and information, and provide services. concrete, helping each other and helping in society. These values in addition to empowering the community, also have an impact on conflict resolution.